(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Endometriosis is a chronic, estrogen-dependent gynecological disorder characterized by the ectopic implantation of endometrial tissue outside the uterine cavity. Although pelvic peritoneum and ovaries are the most frequent sites, urinary tract involvement is rare, accounting for 1–2% of all endometriosis cases, with the bladder being the most commonly affected organ. Urinary bladder endometriosis often presents with non-specific symptoms such as dysuria, urgency, frequency, or hematuria, which may delay diagnosis.The research highlights diagnostic approaches including transvaginal ultrasonography, magnetic resonance imaging, and cystoscopy, as well as therapeutic strategies ranging from hormonal suppression to laparoscopic excision of bladder lesions. Special attention is given to fertility outcomes following surgical management.The study concludes that urinary bladder endometriosis, though uncommon, significantly impacts reproductive health by contributing to infertility through both direct and indirect mechanisms. Early detection and multidisciplinary management are crucial for improving both quality of life and fertility outcomes in affected women.